Diffraction of Microwaves Along the Axis of Propagation Behind Conducting and Dielectric Rods and A Plastic Prism - Young, Willard A. (My University, 1963)
Scope and Contents: The first chapter of this thesis consists of a general introduction and a brief description of previous work done in this same laboratory. Also included is a preliminary description of the present experiment. This is followed, in Chapter 2, by a detailed description of the experimental apparatus. The third and last chapter contains a description of the procedure used in obtaining results, as well as the results themselves. Measurements were made of the diffraction patterns of a plastic prism, and five rods in a total of nine different cases. In all cases, the intensity measurements were made along the axis of propagation of the incident beam behind the diffracting object. A polarization normal to the axis of the rods was used. Theoretical calculations were made in three cases, and compared with the experimental results.
Diffraction of Microwaves
Keywords: Diffraction, Microwaves, Axis of propagation, dielectric rods, plastic prism, diffraction of microwaves